Implementasi Bahasa Pemrograman untuk Perhitungan dan Penggambaran Menggunakan Data Lapangan Hasil Pengukuran Dengan TS - Jasmani Jasmani; Sugianto HP. (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2007)
When the Total Station tilt sensor is activated, automatic correction of vertikal angle and horizontal anglefor mislevelment is displayed. To ensure a precise angle measurement. In case the instrument is used in anunstable situation, constant indexing may be impossible. In this case, the function of tilt correction can bestopped. This adversely affects precision in measurement or survey. Eliminate the parallax by carefully focusingand using diopter adjustment.This instrument can be used for stadia surveying, measurement by stadia is a convenient method formeasuring distances with the stadia hairs of the instrument, in combination with a graduated rod. The stadiainterval is the distance between the top stadia hair reading and the bottom stadia hair reading.